American Image of President Park Chung-hee of the Republic of Korea: Park Chung-heeas Death and American Newspapers - Dr. Lee Young-gwan (Global Journal of Human-Social Science, 2012)
South Korea s President Park Chung-hee was still a controversial figure in Korean history He was a man who achieved the economic miracle of South Korea while adopting repressive measures to suspend the democracy and human Korea The nostalgia of Park s era also remains Park receives fairly good evaluations from the world American newspapers at the death of Park Chung-hee provided the objective views on Park Chung-hee Throughout the newspapers editorials Park was the man who brought the economic miracle of South Korea and a good ally for the U S at the time of Cold War On the other hand he was another dictator who enjoyed autocratic rule under the U S protection The American views provide the foundation to evaluate Park Chung-hee of today